2019
DOI: 10.1111/1756-185x.13487
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B27 prevalence in axial spondyloarthritis patients and in blood donors in a Lebanese population: Results from a nationwide study

Abstract: Aim:To calculate the prevalence of human leukocyte antigen (HLA)-B27 in axial spondyloarthritis patients (axSpA) compared to blood donors (BD) in Lebanon, to identify the clinical and radiological findings associated with HLA-B27 and to estimate the proportion of patients fulfilling the clinical arm of the Assessment of the Spondyloarthritis International Association (ASAS) criteria. Method:Consecutive Lebanese adult axSpA patients fulfilling the ASAS classification criteria were included from 12 rheumatology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…In a recent study, Ziade et al calculated the prevalence HLA-B27 in axSpA in Lebanon. 18 With the agreement of our findings, they found that the low prevalence of HLA-B27 (41.1%) in axSpA.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent study, Ziade et al calculated the prevalence HLA-B27 in axSpA in Lebanon. 18 With the agreement of our findings, they found that the low prevalence of HLA-B27 (41.1%) in axSpA.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the distribution of HLA-B27 population is various. Higher rates of HLA-B27 were found in ax-SpA patients of North America and Western Europe (80-95%) (8) than in Japan and Arab countries (41-84%) (9,10). Meanwhile, the data for China is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, arthritis, enthesitis, and relevant family history had no association with HLA-B27, which differed from the Chung et al study 8 . These characteristics were not found to significantly associate with HLA-B27 in studies conducted in Turkey 32 and Lebanon 28 . This may be due to different duration of disease, ethnicity, and/or genetics, including HLA-B27 subtype.…”
Section: Discussionmentioning
confidence: 68%
“…The prevalence in our study was comparable to previously reported rates from countries that have comparable HLA-B27 frequency in general population (2–9%) 6 , such as 62% among French combined nr-axSpA and r-axSpA patients 8 , 72.3% among Chinese nr-axSpA patients 27 , and 82% among German AS patients 24 . In contrast, the prevalence among axSpA in the Middle East and among Arab AS patients varies widely from 26% in Lebanon to 91% in Turkey 5 , 28 , and the HLA-B27 frequency in general population in these countries ranges from 3 to 14% 6 . Moreover, there was a higher frequency of HLA-B27 among r-axSpA than among nr-axSpA 24 , and AS had a higher prevalence of HLA-B27 than any other SpA diseases 6 , which is consistent with the present study.…”
Section: Discussionmentioning
confidence: 93%